Assessing the Bonitet of Cadastral Parcels for Land Reallocation in Urban Consolidation - Jelena Kilić Pamuković; Katarina Rogulj; Nikša Jajac (Land, 2020)
Cadastral parcels valuation is a very important aspect when defining the priorities for the selection of newly formed parcels in the reallocation processes. Land reallocation involves a new redistribution of land parcels in the project implementation area. In doing so, it is necessary to take into account the preferences of private owners, the value of cadastral parcels, and their bonitet values, whose determination is the basic task of this research. The main goal is to propose a model to assess the bonitet of private cadastral parcels based on Expert System (ES) of fuzzy logic within the knowledge component, which would reduce uncertainty and increase the objectivity of the evaluation. Expert knowledge is included in the evaluation process by defining weighting coefficients for optimizing the rule base, and linear and nonlinear value functions for criteria standardizing. By applying the newly formed ES in the bonitet assessment, with the created base of expert knowledge, the processes of estimating attribute values have been improved, especially in the form of reducing uncertainty in the assessment of urban land parcels, as well as increasing objectivity by involving a group of experts in the model creation. The proposed model also provides equal access to all stakeholders in the process of urban renewal with different requirements and desires. The model also provides support in conducting the negotiation procedures and planning of land reallocation implementation. The proposed model was tested on the field of the construction of the Campus of University of Split.